The effect of fluid-aided modification on the Sm-Nd and Th-Pb geochronology of monazite and bastnäsite: Implication for resolving complex isotopic age data in REE ore systems. (1st May 2021) - Li, Xiao-Chun; Yang, Kui-Feng; Spandler, Carl; Fan, Hong-Rui; Zhou, Mei-Fu; Hao, Jia-Long; Yang, Yue-Heng
Abstract: Isotopic dating studies have revealed that many carbonatite-related REE ore systems have protracted and complex temporal evolution histories. The mechanisms that cause these complex dating results remain poorly understood. Here, we present an in-situ Sm-Nd and Th-Pb isotopic investigation of monazite and bastnäsite from a geologically-complicated deposit, the world-class Bayan Obo REE deposit of China, with the aim of defining the general mechanisms accounting for the protracted age spread observed in this and many other REE deposits. Monazite and bastnäsite are two principle REE ore minerals in the Bayan Obo deposit. Most of the studied monazite and bastnäsite grains have experienced fluid-aided modification. The modified grains have generally homogeneous Sm and Nd contents and Sm-Nd isotopic compositions, implying low mobility of Sm and Nd during the modification process. Thus, the Sm-Nd chronometer can be used to constrain the primary crystallization timing of the REE minerals at 1293 ± 48 Ma. However, altered REE minerals have apparent 208 Pb- 232 Th ages (1248–261 Ma) that are variably younger than the primary crystallization age. In most samples, Th contents have no correlations with 208 Pb- 232 Th ages, while Pb contents tend to decrease along with the younging trend of 208 Pb- 232 Th ages. NanoSIMS mapping shows that 208 Pb and 208 Pb/ 232 Th are heterogeneous, and irregularly distributed in the altered grains. Such results are indicative of variable Pb loss during the fluid-aided modification process. Thus, many Th-Pb ages represent partial isotopic resetting and, hence, are geologically meaningless. Completely reset ages cluster at 450–400 Ma or 280–260 Ma, representing two discrete episodes of post-ore hydrothermal activity. Small amounts of monazite and bastnäsite that were newly crystallized during these two overprinting episodes have initial Nd isotopic signatures approaching the time-evolved isotopic compositions of primary ores, which suggests insignificant REE input to the primary ores during these events. This study provides critical evidence to resolve complex dating results and disparate ore genesis models for the giant Bayan Obo deposit. Moreover, our results indicate the resistance of Sm-Nd isotopes, but the susceptibility of Th-(U)-Pb isotopes, to fluid-aided modification. Therefore, younger Th-U-Pb dates in geologically-complicated deposits should be treated with caution as they may represent partial resetting results and/or may not represent events of increased metal tenor.